Study on Density and morphometrics of seagrass Enhalus acoroides from Different Substrates on Coastal Waters of Tongkeina, City of Manado - Metris S. Wangkanusa; Khristin I. F. Kondoy; Ari B. Rondonuwu (Jurnal Ilmiah PLATAX, 2017)
This research was conducted in coastal waters of Tongkeina, Bunaken Sub-district, Manado City, North Sulawesi. The purpose of this research is to know the density and morphometric characters of seagrass, Enhalus acoroides on different substrates in Tongkeina waters. Data collection was conducted by using quadrant transect method. At the location of the study, three data retrieval points consist of muddy substrate, muddy sand substrate, and rubble were established. To collect data, 6 quadrant transects were lied down parallel to the coastline along the seagrass bed with a total distance of 50 m while the distance of 10 m between quadrant were applied. At each sampling point a 50 cm x 50 cm quadrant transect is placed systematically on 6 points in the each sub-station. Density observation was done by counting the number of seagrass stands on the transect at each observation point at each station. Pictures were taken with a waterproof camera and were classified accordingly based on the size of the squares. The highest numbers seagrass and morphometric characters of seagrass were found on the muddy substrate.  This is because the substrate relatively in quiet waters and the growth of the seagrass is more concentrated on the length and width of the leaf. While the peak of the leaf blade is often eroded by the wave energy and the openness of the study site to the tides in relatively shallow waters, it could be also caused by environmental factors such as the strong currents that obtained at these stations. This fact also contributing to cause the growth of seagrasses is centered on leaves and roots as a form to defend themselves on fine sediments. Density and morphometric of seagrass such as leaf length, leaf width, and root length on the substrate indicate significant value or show a relationship.Keyword : Density,  morphometrics, seagrassABSTRAKPenelitian ini dilaksanakan di perairan pantai Tongkaeina Kecamatan Bunaken Kota Manado Sulawesi Utara. Tujuan dari penelitian ini yaitu untuk mengetahui Kerapatan dan  karakter morfometrik Lamun Enhalus acoroides pada substrat yang berbeda di perairan Tongkeina. Manfaat yang diharapkan dari penelitian ini dapat menjadi sumber informasi dan mampu memberikan kontribusi bagi upaya pengelolaan Lamun Enhalus acoroides di Desa Tongkeina di masa yang akan datang. Pengambilan data dilakukan dengan menggunakan metode transek kuadran. Pada lokasi penelitian, di tentukan tiga titik pengambilan data, yaitu substrat berlumpur, substrat pasir berlumpur, dan pecahan karang (rubble). Pada setiap kedalaman diletakkan 6 transek ulangan kuadran sejajar dengan garis pantai sepanjang areal lamun dengan jarak 50 m sedangkan jarak antara kuadran 10 m. Pada tiap stasiun untuk pengambilan sampel diletakan secara sistematis transek kuadran 1 x 1 sebanyak 6 titik pada tiap sub-stasiun. Untuk pengamatan kerapatan dilakukan dengan menghitung jumlah tegakan lamun dalam transek pada setiap titik pengamatan pada setiap stasiun. Kemudian mengambil gambar dengan kamera kedap air dan gambar diambil sesuai dengan ukuran kuadrat. Kerapatan dan morfometrik lamun tertinggi ditemukan pada substrat berlumpur, hal ini disebabkan karena pada substart belumpur perairannya relatif  tenang dan pertumbuhan lamun lebih terpusat pada panjang dan lebar daun. Sedangkan puncak dari helaian daun seringkali terkikis oleh energi gelombang dan keterbukaan terhadap pasang surut pada perairan yang relatif dangkal juga disebabkan oleh faktor lingkungan seperti arus yang kuat didapatkan pada stasiun ini menyebabkan pertumbuhan lamun terpusat pada  daun dan akar untuk mempertahankan diri pada sedimen halus. Kerapatan dan morfometrik lamun seperti panjang daun, lebar daun, dan panjang akar terhadap substrat menunjukkan nilai yang signifikan atau memperlihatkan adanya hubungan.Kata kunci:      Kerapatan, morfometrik, lamun.